TANGGUNG JAWAB PEJABAT PEMBUAT AKTA TANAH (PPAT) ATAS PEMBUATAN AKTA JUAL BELI TERHADAP HARGA JUAL YANG BELUM LUNAS (STUDI PUTUSAN NOMOR. 1515 K/PDT/2016) - JUANTHA DHARMA PUTRA BARUS (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING1. Budiman Ginting2. T. Keizerina Devia3. SuprayitnoLand title transfer is commonly found in our community. The capacity and the authority to do the transfer are in the hand of a profession/position which is known in the Indonesian law as PPAT (Officials Empowered to Draw up Land Deeds) who have the authority to draw up authentic deeds in Land Title or Apartment Ownership. This profession does not belong to the position in the State’s structure but it is an independent profession. It means that the position of a PPAT does not depend on any party and even on the State. In doing his job, a PPAT obtains earnings/fee based on the products he has yielded, authentic deeds.The deed of a PPAT is made as evidence that a certain legal act has been carried out concerning Land Title and Apartment Ownership. One of types of Deed made before a PPAT is Sale & Purchase Contract. Buy and sell are an agreement in which a party binds himself to submit a certain thing and the other party pays for it. Sale & Purchase contract made before a PPAT is the formulation from the parties which is embodied in it. In the transaction, the delivery of goods and its payment are done transparently and in cash. Therefore, the goods which will be delivered, along with the price are mentioned in the Deed so that in the formulation of the Sale & Purchase contract, a PPAT is required to use prudential principles in embodying the willingness of the parties to the Deed in order to be protected against any claim from the authorities.Keywords: Officials Empowered Draw up Land Deeds, Authentic Deed, Sale & Purchase